Is higher government efficiency bringing about higher innovation? - Wen, Jun; Deng, Peidong; Zhang, Qianxiao; Chang, Chun-Ping (Technological and Economic Development of Economy, 2021)
This research analyzes the impact of government effectiveness on innovation by using unbalanced panel data from the World Bank on 166 countries spanning 1996 to 2018. We analyze the impact of government efficiency on innovation through various panel fixed-effects models, while incorporating control variables such as GDP, education, and industrial structure into the analysis framework. The empirical results conclude that, in our selected countries, government efficiency has a significantly positive impact on innovation output and more importantly verify the positive impact from the improvement of bureaucracy quality on innovation. The evidence again shows the positive impacts of government efficiency on innovation output by addressing endogenous and robustness checking via the series of methods. Furthermore, the heterogeneity and mechanism of this relationship would be explored. Therefore, the research results provide an alternative method for national governments to promote innovation output by improving government effectiveness.